Unraveling dystonia circuitry in rodent models using novel neuromodulation techniques - Lisa Rauschenberger; Chi Wang Ip (Dystonia, 2024)
Dystonia is a network disorder presumed to result from abnormalities in multiple brain regions and in multiple cell populations. The specific pathomechanisms affecting the motor circuits in dystonia are, however, still largely unclear. Animal models for dystonia have long been used to advance our understanding on how specific brain regions and cell populations are involved in dystonia symptomatogenesis. Lesioning, pharmacological modulation and electrical stimulation paradigms were able to highlight that both the basal ganglia and the cerebellum are pathologically altered in these animal models for dystonia. Techniques such as optogenetics and chemogenetics now offer the opportunity for targeted modulation of brain regions and most importantly cell populations and circuits. This could not only allow for a better understanding of the dystonic brain, but potentially improve and expand treatment options. In hopes that the insights from these neuromodulation techniques will eventually translate into therapies, we aim to summarize and critically discuss the findings from different in vivo approaches used to dissect the network dysfunctions underlying dystonia.